2017
DOI: 10.1101/gr.216754.116
|View full text |Cite
|
Sign up to set email alerts
|

Identifying cis-mediators for trans-eQTLs across many human tissues using genomic mediation analysis

Abstract: The impact of inherited genetic variation on gene expression in humans is well-established. The majority of known expression quantitative trait loci (eQTLs) impact expression of local genes (cis-eQTLs). More research is needed to identify effects of genetic variation on distant genes (trans-eQTLs) and understand their biological mechanisms. One common trans-eQTLs mechanism is “mediation” by a local (cis) transcript. Thus, mediation analysis can be applied to genome-wide SNP and expression data in order to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…Mediation analysis has recently been used with genomic data, including in humans (e.g., [10,15]) and rodents (e.g., [51,81]), to identify and refine potential intermediates of causal paths underlying phenotypes. We use a similar genome-wide mediation analysis as used with the DO [22, 33] to detect mediators of eQTL effects on gene expression.…”
Section: Mediation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Mediation analysis has recently been used with genomic data, including in humans (e.g., [10,15]) and rodents (e.g., [51,81]), to identify and refine potential intermediates of causal paths underlying phenotypes. We use a similar genome-wide mediation analysis as used with the DO [22, 33] to detect mediators of eQTL effects on gene expression.…”
Section: Mediation Analysismentioning
confidence: 99%
“…In human data, co-occurence of QTL across various multi-omic data has been used to assess potentially related and connected biological processes; examples include gene expression with chromatin accessibility [7] or regulatory elements [8], and ribosome occupancy with protein abundances [9]. More formal integration through statistical mediation analyses has also been used to investigate relationships between levels of human biological data, such as distal genetic regulation through local gene expression [10,11], and eQTL with regulatory elements [12][13][14] and physiological phenotypes, such as cardiometabolic traits [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that trans-eQTLs are likely involved in indirect regulations, where the trans-eGene can be mediated by the cis-eGene, which is known as the mediation effect (Pierce et al, 2014;Brynedal et al, 2017;Yang et al, 2017;Yao et al, 2017). These studies provide evidence of a cismediated mechanism that explains distal regulation of trans-eGenes by trans-eQTLs (Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 86%
“…Expression prediction in DePMA hinges on assessing distal-eSNPs for inclusion in the design matrix via mediation analysis, adopting methods from previous studies [10,11,13]. We first split data for gene expression, SNP dosages, and any potential mediators into k training-testing splits.…”
Section: Transcriptomic Prediction Using Depmamentioning
confidence: 99%
“…This result accords with Boyle et al's omnigenic model, proposing that regulatory networks are so interconnected that a majority of genetic variants in the genome, local or distal, have indirect effects on transcription of any particular gene [6,7]. Many groups have leveraged this model to identify distal expression quantitative trait loci (eQTLs) by testing the effect of a distal-eSNP on an eGene mediated through a set of genes local to the SNP, concluding that many distal-eQTLs are often eQTLs for many local genes [8][9][10][11][12][13]. It has been shown previously that distal-eQTLs found in regulatory hotspots are generally cell-type specific [8,12,14].…”
Section: Introductionmentioning
confidence: 99%